Determinants Of Financial Performance In People's Credit Banks In Bali Province - MARTINIASIH, Putu Mas; TRIMURTI, Christimulia Purnama; KOMALASARI, Yeyen; ADINEGARA, Gusti Ngurah Joko (Journal of Entrepreneurial and Business Diversity, 2024)
Purpose: This research aims to determine and analyze the influence of the Loan Deposit Ratio, operating costs, operating income, Non-Performing Loans, Capital Adequacy Ratio and Net Interest Margin on the financial performance of BPRs in Bali Province in 2019-2022.Methodology:This research is quantitative descriptive. This research was conducted at all Rural Banks in Bali Province by analyzing the Determinants of Financial Performance at Rural Banks in Bali Province from November 2023 to January 2024. The scope of the research is to determine the factors that influence Financial Performance at Rural Banks in Bali Province. The population in this research is all Rural Banks in Bali Province in 2019-2022, totaling 135 Rural Banks. Sampling in this research used the purposive sampling method.Findings: The calculations show that the total research sample was 133 Rural Banks in Bali Province, with four years of observation totaling 532 data. The analysis technique used is multiple linear regression analysis. The research results show that the Loan to Deposit Ratio (LDR) positively affects Return on Assets (ROA).Implication:Operating Costs Operating Income (BOPO) hurts Return on Assets (ROA). Non-performing loans (NPL) hurt Return on Assets (ROA). Capital Adequacy Ratio (CAR) positively affects Return on Assets (ROA). Net Interest Margin (NIM) has a negative effect on Return on Assets (ROA).